2008
DOI: 10.1021/np070590f
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Metabolites from the Plant Endophytic Fungus Pestalotiopsis foedan

Abstract: Pestafolide A ( 1), a new reduced spiro azaphilone derivative, and pestaphthalides A ( 2) and B ( 3), two new isobenzofuranones, have been isolated form solid cultures of an isolate of Pestalotiopsis foedan. The structures of these compounds were determined mainly by analysis of their NMR spectroscopic data. The relative configuration of 1- 3 was assigned by analysis of (1)H NMR J-values and NOESY data, and the absolute configuration was determined by application of the CD excitation chirality and modified Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
92
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 134 publications
(98 citation statements)
references
References 35 publications
6
92
0
Order By: Relevance
“…However, biology and ecology of most endophytes are not known but are assumed to vary according to host and environment [7,8,38]. A huge number of authors suggested that endophytes are good sources of novel secondary metabolites that possess antibacterial [37,65] antifungal [15,65] and anticancer properties [36]. In this study, the endophytic mycobiota of the medicinal plant Tinospora cordifolia Miers., was studied.…”
Section: Introductionmentioning
confidence: 97%
“…However, biology and ecology of most endophytes are not known but are assumed to vary according to host and environment [7,8,38]. A huge number of authors suggested that endophytes are good sources of novel secondary metabolites that possess antibacterial [37,65] antifungal [15,65] and anticancer properties [36]. In this study, the endophytic mycobiota of the medicinal plant Tinospora cordifolia Miers., was studied.…”
Section: Introductionmentioning
confidence: 97%
“…(5)(6)(7)(8) Peneciraistin C (Pe-C) ( Fig. 1) is a novel spiroketal compound purified from the fungus Penicillium raistrickii, isolated from saline soil collected in Bohai Bay in Zhanhua (Shandong Province, China).…”
mentioning
confidence: 99%
“…The NOE (Fig. 2) interaction observed between H a ÀC(6) (d(H) 2.78 (d, J ¼ 16.0)) and HÀC(4), along with no NOE interaction observed between H a ÀC(6) and Me (15) (14) suggested that Me (14) should be b-configurated. Because of some significant signal overlap, we tried to crystallize 1 in different solvents and finally failed to obtain suitable crystals.…”
mentioning
confidence: 95%